Onset of Action and Efficacy of Ibuprofen Liquigel as Compared to Solid Tablets: A Systematic Review and Meta-Analysis - Lawati, Hanan Al; Jamali, Fakhreddin (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
Purpose. Ibuprofen liquigel has been believed to provide faster analgesic effect. However, comparative studies evaluating the efficacy of liquigel versus regular tablets are not available. Hence, we carried out a systematic review and a meta-analysis to compare the onset of action and efficacy of over-the-counter doses of ibuprofen liquigel (IBULG) vs ibuprofen tablets (IBUT). Methods. Published clinical trials of IBULG and IBUT were identified through a systematic search of various data bases up to October, 2015. Results. In total 18 eligible studies on IBUT and 4 on IBULG were found. There was no significant difference in the median time to the first perceptible pain relief or the proportion of patients with more than 50% pain relief between the two products. However, IBULG yielded significantly greater odd ratios in meaningful pain relief at 60, 90 and 120 min, but not at 30 min, as compared with IBUT. Conclusion. The available evidence, although not overwhelming, suggest a faster onset of analgesia for liquigel as compared with tablets. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.